1989
DOI: 10.1093/jac/24.suppl_a.101
|View full text |Cite
|
Sign up to set email alerts
|

Activity of meropenem, against Gram-positive bacteria

Abstract: A new carbapenem antibiotic, meropenem, was shown to be active against a large number of Gram-positive bacteria. The drug inhibited penicillinase-positive and -negative, methicillin-susceptible staphylococti equally well. Among the comparative antimicrobials examined, only Af-formimidoyl-thienamycin (imipenem) was two to four times more active than meropenem. Compared with vancomycin or methicillin, meropenem was 10-20 times more active. Strains of 11 species of streptococci were highly susceptible to meropene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…This may explain the overgrowth of this strain in the ciprofloxacin and enoxacin time-kill studies, especially as the development of quinolone resistance has been reported to be due to single-step mutations (15). A notable property of the fluoroquinolones is the reported low rate of bacterial mutation to resistance (6).…”
Section: Discussionmentioning
confidence: 97%
“…This may explain the overgrowth of this strain in the ciprofloxacin and enoxacin time-kill studies, especially as the development of quinolone resistance has been reported to be due to single-step mutations (15). A notable property of the fluoroquinolones is the reported low rate of bacterial mutation to resistance (6).…”
Section: Discussionmentioning
confidence: 97%
“…Fluoroquinolone uptake studies were also performed to investigate the possibility of active, energydependent transport mechanisms in S. aureus ATCC 29213. Uptake studies indicated that active efflux does occur in S. aureus ATCC 29213.The antistaphylococcal activity of fluoroquinolones under aerobic conditions has been well established through numerous studies (13,24). However, the antistaphylococcal activity of these antimicrobial agents under anaerobic conditions has not been well studied.…”
mentioning
confidence: 99%
“…The antistaphylococcal activity of fluoroquinolones under aerobic conditions has been well established through numerous studies (13,24). However, the antistaphylococcal activity of these antimicrobial agents under anaerobic conditions has not been well studied.…”
mentioning
confidence: 99%
“…Ciprofloxacin has been shown to have activity in vitro against enterococci (6,7,15) and has been used in treating enterococcal infections (3, 5). Although relatively high MICs and the existence of an inoculum effect have been noted, resistance to ciprofloxacin has been uncommon (6,7,11,15,21).In both the acute-care and long-term-care facilities of the Ann Arbor Veterans Affairs Medical Center, the majority of enterococci have high-level resistance to aminoglycosides (22,23). We determined whether resistance to ciprofloxacin among enterococcal isolates had increased from 1985 and 1986 to 1989 and 1990.…”
mentioning
confidence: 99%
“…In recent years, increasing resistance to aminoglycosides (22), penicillins (1), and.vancomycin (18) has been noted. Ciprofloxacin has been shown to have activity in vitro against enterococci (6,7,15) and has been used in treating enterococcal infections (3, 5). Although relatively high MICs and the existence of an inoculum effect have been noted, resistance to ciprofloxacin has been uncommon (6,7,11,15,21).…”
mentioning
confidence: 99%